1D Alignment of PEDOT in a Buckypaper for High‐Performance Solid Supercapacitors. Issue 9 (21st June 2016) - Soni, Roby; Anothumakkool, Bihag; Kurungot, Sreekumar
Abstract: A flexible solid‐state supercapacitor is prepared from carbon nanotube (CNT)‐based buckypaper after forming a thin layer of polyethylenedioxythiophene (PEDOT) on the surface of the CNTs in the paper. A highly conducting PEDOT phase is obtained by interfacial polymerization, in which polymerization is confined at the interface of two immiscible liquids. The hydrophilic interaction between the functionalized CNTs and the oxidizing agent (iron perchlorate, Fe(ClO4 )3 ), which is located in the aqueous phase, and the restricted interaction of the oxidizing agent with the EDOT monomer in the organic layer at the immiscible interface play a vital role in establishing a uniform and aggregate‐free growth pattern of PEDOT on CNT. By carefully optimizing the amount of polymer in the paper, an electrode with a sheet resistance of 3.4 Ω □ −1 and equivalent series resistance of 0.95 Ω can be prepared. A thin and flexible solid‐state supercapacitor device with an overall thickness of 210 μm is made by using this paper as the electrodes and poly(vinyl alcohol)/lithium chloride as the gel electrolyte. The power density and energy density of the electrode are 9.94 W cm −3 and 8.85 mWh cm −3, respectively. The device also delivers a high volumetric capacitance of 18 F cm −3 and areal capacitance of 354 mF cm −2 . The demonstrated strategy is scalable and hence the process can be conveniently applied to prepare large‐area PEDOT‐modified buckypapers in a short time. Abstract : Thin and flexible : A thin, flexible solid‐state supercapacitor (see figure) fabricated from electrodes made of a buckypaper, the carbon nanotubes of which are coated with surface‐aligned polyethylenedioxythiophene, and a poly(vinyl alcohol)/lithium chloride gel electrolyte delivered high performance in bent and unbent states and under various current dragging conditions.